The prevalence and peculiarities of the clinical course of periodontal tissue diseases in persons with primary hypothyroidism - Chornii, Arsenii; Shmanko, V. V. (Journal of Education, Health and Sport, 2017)
The article presents the results of clinical dental examination of persons with primary hypothyroidism. The analysis of the research showed that they have a high prevalence of periodontal tissue diseases (93.25%), which was manifested by the development of inflammatory and, to a greater extent, inflammatory and dystrophic lesions of its tissues, which occurred in a chronic latent form.